Sodium channel β2 subunit promotes filopodia-like processes and expansion of the dendritic tree in developing rat hippocampal neurons - Maschietto, Marta; Girardi, Stefano; Dal Maschio, Marco; Scorzeto, Michele; Vassanelli, Stefano (Frontiers in Cellular Neuroscience, 2013)
The b2 auxiliary subunit of voltage gated sodium channels (VGSCs) appears at early stages of brain development. It is abundantly expressed in the mammalian central nervous system where it forms complexes with different channel isoforms, including Nav1.2. From the structural point of view, b2 is a transmembrane protein: at its extracellular N-terminus an Ig-like type C2 domain mediates the binding to the pore forming alpha subunit with disulfide bonds and the interactions with the extracellular matrix. Given this structural versatility, b2 has been suggested to play multiple functions ranging from channel targeting to the plasma membrane and gating modulation to control of cell adhesion. We report that, when expressed in Chinese Hamster Ovary cells CHO-K1, the subunit accumulates at the perimetral region of adhesion and particularly in large lamellipodia-like membrane processes where it induces formation of filopodia-like structures. When overexpressed in developing embryonic rat hippocampal neurons in vitro, b2 specifically promotes formation of filopodia-like processes in dendrites leading to expansion of the arborisation tree, while axonal branching remains unaltered. In contrast to this striking and highly specific effect on dendritic morphology, the targeting of functional sodium channels to the plasma membrane, including the preferential localization of Nav1.2 at the axon, and their gating properties are only minimally affected. From these and previously reported observations it is suggested that b2, among its multiple functions, may contribute to promote dendritic outgrowth and to regulate neuronal wiring at specific stages of neuronal development.